Evaluation of different gyroscope sensors for smart wheelchair applications - Chua, J. J. C.; Fuss, F. K.; Subic, A. (Procedia Engineering, 2011)
Inertial sensors have been used extensively in recent years for measuring and monitoring performance in many different sports except in wheelchair sports. Mounting an accelerometer directly on a wheelchair frame and determining performance parameters from linear acceleration measurements can provide valuable insight into wheelchair sports performance. However, the processing required for this purpose is tedious. With improvements in the accuracy and measuring range of MEMS gyroscopes, it is now possible to mount a gyroscope on a wheelchair racing wheel and measure speeds close to 30m/s. This paper evaluates and compares angular velocity measurements from a custom built wireless gyroscope sensor, a commercial inertial sensor and an iPod Touch 4 device. With effective filtering, gyroscope sensors provide a suitable tool for performance analysis in wheelchair sports.